Intravenous amantadine for freezing of gait resistant to dopaminergic therapy: a randomized, double-blind, placebo-controlled, cross-over clinical trial. - Young Eun Kim; Ji Young Yun; Hui June Yang; Han-Joon Kim; Namyi Gu; Seo Hyun Yoon; Joo-Youn Cho; Beom S Jeon (PLoS ONE, 2012)
Freezing of gait (FOG) is one of the most disabling symptoms in Parkinsonism. Open-label studies have suggested that intravenous (IV) amantadine is effective against FOG resistant to dopaminergic therapy in Parkinson's disease (PD). We evaluated the efficacy of IV amantadine on FOG resistant to dopaminergic therapy.This was a randomized, double-blind, placebo-controlled, cross-over study on IV amantadine. The placebo (normal saline) and amantadine (400 mg/day) were injected for 2 days with a 52-hour washout period. The instruments for the outcome measures were the Freezing of Gait Questionnaire (FOGQ), Unified Parkinson's disease rating Scale (UPDRS), and the duration of the 4×10 m walking test. The placebo arm was compared to the amantadine arm. Ten patients were enrolled but two patients withdrew, one from each arm. The FOGQ and UPDRS scores and the duration of the 4×10 m walking test improved in both arms compared to the baseline (P<0.05 in all). However, there were no differences in these values between the amantadine arm and placebo arm (P = 0.368, P = 0.583, P = 0.206, respectively). Follow-up measures 2 weeks after discharge in an open-label study showed the beneficial effects of an amantadine tablet on FOG (FOGQ, P = 0.018; UPDRS, P = 0.012 respectively).This double blind, placebo-controlled study did not show the efficacy of IV amantadine on FOG when compared with the placebo. This study provides Class II evidence due to small sample size for the lack of benefit of IV amantadine on FOG resistant to dopaminergic therapyClinicaltrials.gov NCT01313819.